Stress-responsive feelscape addressing the effects of urban ambient stress on the pedestrians of Taytay Municipality through an adapted urban acupuncture intervention - Diestro, Connie Paula D.R
Taytay is a first class urban municipality in the province of Rizal, proximate to Metro Manila. As a result of its rapid urbanization, there is a highly stressful environmental condition that threatens the well-being of pedestrians in the locality. From a pedestrian's vantage point, the hitches of everyday commute and the outdoor grind such as traffic, noise, pollution, narrow streets and ill-maintained urban facilities, among others, can be problematic on a daily basis. These chronic environmental conditions, conceived as ambient stress, although not urgent, impinge on "human functioning at nearly all levels - physiology, motivation, affect, behavior, cognition, and social interaction" (Campbell, 1983). Stress, highlighted by the World Health Organization as one of the major challenges of the 21st century, links urban living as its major contributor (Adli, 2011). The linkage on urban living and stress emphasize the need for restorative and responsive design solutions that are supplemental both to a country's development and its people's well-being. In line with this, the study analyzes the urban social environment of Taytay, Rizal and comes up with an adapted urban acupuncture landscape design intervention that alleviates the stressful condition of the pedestrian realm through specific problem-focused and emotion-focused coping solutions and warrants positive community reappraisal through time-share activities allowing optimal use of the landscape.